Risk of preterm birth in the subsequent pregnancy following caesarean section at full cervical dilatation compared with mid‐cavity instrumental delivery. (12th September 2019) - Wang, Mandy; Kirby, Adrienne; Gibbs, Emma; Gidaszewski, Beata; Khajehei, Marjan; Chua, Seng C.
Abstract : Background: Expediting delivery in the second stage of labour often involves a choice between a caesarean section at full dilatation or mid‐cavity instrumental delivery. Accumulating evidence suggests that the mode of delivery may influence the risk of preterm birth in the subsequent pregnancy. Aims: To directly compare first birth caesarean section at full dilatation with mid‐cavity instrumental delivery for the risk of preterm birth in the subsequent pregnancy (second birth). A further aim was to identify predictive factors associated with these index modes of delivery. Materials and Methods: This is a retrospective cohort study involving three maternity hospitals in western Sydney over the period of 2006–2017. Inclusion criteria were nulliparous women with a singleton term cephalic first birth delivered by caesarean section at full dilatation or mid‐cavity instrumental delivery, and whose second birth also occurred under our care. Data were analysed separately for first and second births. Results: There were 425 caesarean section at full dilatation and 874 mid‐cavity instrumental cases which met inclusion criteria. The risk of preterm birth in the second birth was 5.7% compared to 3.2%, respectively (risk ratio 1.76; 95% CI 1.04–3.00; P  =   0.035). After excluding causes of preterm birth not related to previous mode of delivery, the risk of spontaneous preterm birth was 4.3% compared to 2.0%, respectively (risk ratio 2.18; 1.14–4.19; P  =   0.019). Conclusion: Caesarean section at full dilatation is associated with a significantly higher rate of preterm birth in the subsequent pregnancy compared to a mid‐cavity instrumental delivery. This should be considered in second‐stage mid‐cavity decision‐making.